Functional analysis and localisation of a thyrotropin-releasing hormone-type neuropeptide (EFLa) in hemipteran insects - Kotwica-Rolinska, Joanna; Krištofová, Lucie; Chvalová, Daniela; Pauchová, Lucie; Provazník, Jan; Hejníková, Markéta; Sehadová, Hana; Lichý, Martin; Vaněčková, Hana; Doležel, David (Insect biochemistry and molecular biology, 2020)
EFLamide (EFLa) is a neuropeptide known for a long time from crustaceans, chelicerates and myriapods. Recently, EFLa-encoding genes were identified in the genomes of apterygote hexapods including basal insect species. In pterygote insects, however, evidence of EFLa was limited to partial sequences in the bed bug (Cimex), migratory locust and a few phasmid species. Here we present identification of a full length EFLa-encoding transcript in the linden bug, Pyrrhocoris apterus (Heteroptera). We created complete null mutants allowing unambiguous anatomical location of this peptide in the central nervous system. Only 2-3 EFLa-expressing cells are located very close to each other near to the surface of the lateral protocerebrum with dense neuronal arborization. Homozygous null EFLa mutants are fully viable and do not have any visible defect in development, reproduction, lifespan, diapause induction or circadian rhythmicity. Phylogenetic analysis revealed that EFLa-encoding transcripts are produced by alternative splicing of a gene that also produces Prohormone-4. However, this Proh-4/EFLa connection is found only in Hemiptera and Locusta, whereas EFLa-encoding transcripts in apterygote hexapods, chelicerates and crustaceans are clearly distinct from Proh-4 genes. The exact mechanism leading to the fused Proh-4/EFLa transcript is not yet determined, and might be a result of canonical cis-splicing, cis-splicing of adjacent genes (cis-SAG), or trans-splicing.
Keywords: Male; fylogeneze; neuropeptidy; Phylogeny; hmyzí proteiny; Amino Acid Sequence; Thyrotropin-Releasing Hormone; mužské pohlaví; sekvenční seřazení; In silico peptide prediction; Null mutant; Animals; ženské pohlaví; TRH; hormon uvolňující thyreotropin; zvířata; sekvence aminokyselin; Insect Proteins; Female; EFLamide; Alternative splicing; Heteroptera; Neuropeptides; Sequence Alignment; CRISPR/Cas9